Pass the ball, Mo! - Adler, David A.; Ricks, Sam (Penguin Young Readers, an imprint of Penguin Random House LLC, 2018)
With the big game coming up, Mo Jackson, the shortest member of the basketball team, is determined to learn how to pass the ball in time to help his team win.
Keywords: Basketball players -- Fiction; Size -- Fiction; African Americans -- Fiction; Basketball players -- Juvenile fiction; Size -- Juvenile fiction; African Americans -- Juvenile fiction